Efficiency of the main application of fertilizers and top dressing of eggplant under drip irrigation on ordinary chernozems of the Rostov region - V. A. Borisov; A. M. Menshikh; V. S. Sosnov (Овощи России, 2024)
Relevance. Fertigation is the application of fertilizers, in which nutrients are dissolved in water for irrigation. This method is relevant when growing eggplant in the Rostov region, allowing effective use of fertilizers, since nutrients enter directly into the roots of plants, which eliminates their loss to evaporation or weathering. During fertigation, there is no need to carry out separate procedures for fertilization and irrigation, operations are combined into one, which reduces time and costs. The Rostov region is characterized by variable climatic conditions, including drought and strong winds. Fertigation ensures uniform and constant nutrition of plants, allowing them to better adapt to weather conditions, and can help increase yields by optimizing plant growth and development conditions.Material and methodology. In the conditions of the Rostov region, on ordinary heavy loamy chernozems, studies were conducted on the cultivation of eggplant on different backgrounds of the main application of mineral fertilizers in calculated doses before planting and using root fertilizing with complex fertilizers with trace elements with irrigation (fertigation), as well as leaf fertilizing with organomineral fertilizer Arksoil during the growing season.Results. It was revealed that mineral fertilizers and top dressing accelerated the growth and development of plants, and in the best case, the increase in indicators was 2 times higher compared with the control, while the height of the main stem, the number of lateral shoots and the number of ovaries on the plant, as well as the average weight of the fruit, significantly increased, which ensured an increase in plant productivity. The combined use of basic fertilizer and complex soluble fertilizers in the drip irrigation system has significantly increased plant productivity and increased yields to 77.82 t/ha. The application of high doses of fertilizers in combination with fertigation with water-soluble fertilizers did not actually affect the quality of fruits. The content of dry matter and nitrates remained at an optimal level.